The Effect of pH and Temperature on The Stability of Anthocyanins from Black Soybean Skin Extracts - Sunarya, Risa Rahmawati; Subarkah, Cucu Zenab; Purliantoro, Dwi; Taskinih, Taskinih; Islamiati, Fitri Nur (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Anthocyanins are natural dyes of purple and red. Anthocyanin dyes are applied in various industries as a drink or food coloring. As natural dyes, anthocyanins have an important role in human health. This research aimed to analyze the stability of anthocyanins from black soybean skin extract at varying pH and temperature. Anthocyanins from black soybean skins are macerated using two kinds of solvents. The solvents are distilled water + 30% citric acid and 70% ethanol + 1% HCl. Maceration was carried out at a temperature of 4℃. Then the anthocyanin was treated at a temperature range of 40-90℃ and pH of 5-9 and its absorbance was measured using UV-Vis’s spectrometry. The concentration of anthocyanin from black soybean skins is from the solvent distilled water + 30% citric acid of 1.992 mg/L, while from the solvent 70% ethanol + 1% HCl it was 1.936 mg/L. The color stability temperature t of black soybean skin extract was carried out at temperatures of 40°C, 50°C, 60°C, 70°C, 80°C, and 90°C. with respective absorbance of 0.274; 0.247; 0.237; 0.227; and 0.214. The higher the temperature, the anthocyanin content decreases. pH test was carried out at pH 5, 6, 7, 8, and 9 with respective absorbance values of 1.831; 1,759; 1,229; 1,118; and 1,066. The pH test showed that the higher the pH, the anthocyanin content was reduced, while the application of additional anthocyanin to white agar as food coloring showed that the anthocyanin content was only 0.125. It can be concluded that anthocyanins have good stability at low temperatures and acidic pH.